Alkaloids from Chlidanthus fragrans and their acetylcholinesterase, butyrylcholinesterase and prolyl oligopeptidase activities - Cahlíková, Lucie; Hrabinová, Martina; Kulhánková, Andrea; Benesová, Nina; Chlebek, Jakub; Jun, Daniel; Novák, Zdenĕk; Macáková, Katerina; Kunes, Jirí; Kuca, Kamil; Opletal, Lubomír (Natural product communications, 2013)
Eleven Amaryllidaceae alkaloids (1-11) were isolated from fresh bulbs of Chlidanthus fragrans Herb. The chemical structures were elucidated by MS, and 1D and 2D NMR spectroscopic experiments. Complete NMR assignments were achieved for deoxypretazzetine (1). All compounds were evaluated for their erythrocytic acetylcholinesterase and serum butyrylcholinesterase inhibition activity using Ellman's method. In the prolyl oligopeptidase assay, Z-Gly-Pro-p-nitroanilide was used as substrate. In biological assays, only the crinine type Amaryllidaceae alkaloid undulatine showed promising acetylcholinesterase and prolyl oligopeptidase inhibition activity with IC50 values of 23.0 +/- 1.0 microM and 1.96 +/- 0.12 mM, respectively. Other isolated compounds were considered inactive.
Keywords: serinové endopeptidasy; Serine Endopeptidases; magnetická rezonanční spektroskopie; Acetylcholinesterase; Prolyl Oligopeptidases; alkaloidy amarylkovitých; Butyrylcholinesterase; Liliaceae; acetylcholinesterasa; Amaryllidaceae Alkaloids; Magnetic Resonance Spectroscopy; butyrylcholinesterasa; liliovité; prolyloligopeptidasy